EKSTRAKSI KUERSETIN DARI KULIT TERONG BELANDA (Solanum betaceum Cav.) MENGGUNAKAN PELARUT ETANOL DENGAN METODE MASERASI DAN SOKLETASI - Siswarni MZ; Yusrina Ika Putri; Rizka Rinda Pramasti (Universitas Sumatera Utara, 2017)
The tamarillo peels (Solanum betaceum Cav.) contain flavonoid compounds, quercetin that can serve as antioxidant. This research aims to determine the best condition of operation in tamarillo peels extraction process to obtain the high yield value, and to prove the presence of antioxidant activity quantitatively. The materials used this research are tamarillo peels and ethanol. The independent variables in this research were the concentration of etanol which were 60%, 70%, 80% and 90% for maceration, and 70%, 80%, 90%, 99% for soxhletation. The extraction time are 3 days, 4 days, and 5 days for maceration and 3 hours, 4 hours, 5 hours for soxhletation. Extraction is done by maceration and soxhletation. The results of the qualitative analysis using FTIR represent the presence of functional groups such as keton, arylether, hydroxyl and aromatic rings which indicates quercetin compound’s presence. In quantitative analysis used Spectrofotometry UV-Vis, with the variation of 99% solvent concentration and 5 hours of extraction time for soxhletation, the highest yield value obtained 0,0877 mg/g. The variation of 80% solvent concentration and 5 days of extraction time for maceration, the highest yield value obtained 0,0705 mg/g